DYNAMIC OF FORMATION AND GEOLOGIC-GEOMORPHOLOGICAL FACTORS OF GRAVITATION PROCESSES ACTIVATION IN IRSHAVSKIY REGION OF ZAKARPATSKA AREA - Ivanik, O.; Huda, O. (Visnyk of Taras Shevchenko National University of Kyiv. Geology, 2025)
Detail analysis of the modern exogenic gravitation processes factor activation has been carried out. The main morphological features of the modern and stabilized landslides on the different geomorphological levels have been characterized. There classification features and belonging to the defined lithologic-stratigraphic strata have been defined. The main influence of lithologic-stratigraphic and structural-tectonic factors on the landslide formation has been proved.